The Egyptian Journal of Neurology, Psychiatry and Neurosurgery - Abdulghani, M. Ossama
The Egyptian Journal of Neurology, Psychiatry and Neurosurgery, the official publication of The Egyptian Society of Neurology, Psychiatry and Neurosurgery (ESNPN), is a peer-reviewed, open access journal publishing articles in the field of clinical neurosciences, including neurology, psychiatry and neurosurgery. The journal presents cutting edge research on technical and clinical studies of health, ethical and social issues in the field of clinical neurosciences.  .